Types of Laughter and Crying in Uzbek and English: A Cross-Cultural Analysis - Azimova Muxtasarxon Jaloldin qizi; Majidova Sevinch Shuxrat qizi (Journal of Discoveries in Applied and Natural Science, 2024)
This article delves into the types and cultural significance of laughter and crying in the Uzbek and English languages, exploring how these expressions of emotion reflect broader societal and psychological themes. While laughter and crying are universally experienced, the ways they are expressed, understood, and categorized differ significantly across cultures. In Uzbek culture, laughter and crying often carry meanings that emphasize communal experience and social cohesion, with terms like "qahqaha urish" (hearty laughter) and "yig'lamoq" (crying with shared sentiment) embodying these values (Niyozov, 2021). In English, however, expressions such as "sarcastic laughter" and "tears of joy" are more nuanced, often reflecting individual emotional states or situational factors (Martin, 2019). Using a cross-cultural approach, this study aims to uncover both the universal and unique qualities in the emotional lexicons of Uzbek and English, shedding light on how each language embeds cultural attitudes within expressions of laughter and crying. This analysis offers a deeper understanding of how emotional expressions contribute to identity, community, and interpersonal dynamics.